Social Networks and Labor Market Transitions - Yann Bramoullé; Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2004)
We study the influence of social networks on labor market transitions. We develop the first model where social ties and job status coevolve through time. Our key assumption is that the probability of formation of a new tie is greater between two employed individuals than between an employed and an unemployed individual. We show that this assumption generates negative duration dependence of exit rates from unemployment. Our model has a number of novel testable implications. For instance, we show that a higher connectivity among unemployed individuals reduces duration dependence and that exit rates depend positively on the duration of the last job held by the unemployed worker.
Keywords: J6; E24; Z13; 330; social networks; unemployment duration; labor market transitions; social capital; economic inbreeding; Berufliche Integration; Arbeitslosigkeit; Dauer; Soziales Netzwerk; Arbeitsmobilität; Theorie